2017
DOI: 10.1145/3054177
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy and Survey of Cloud Resource Orchestration Techniques

Abstract: Cloud services and applications prove indispensable amid today’s modern utility-based computing. The cloud has displayed a disruptive and growing impact on everyday computing tasks. However, facilitating the orchestration of cloud resources to build such cloud services and applications is yet to unleash its entire magnitude of power. Accordingly, it is paramount to devise a unified and comprehensive analysis framework to accelerate fundamental understanding of cloud resource orchestration in terms of concepts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 102 publications
0
53
0
1
Order By: Relevance
“…Weerasiri et al [24] lists security as one of the crosscutting concerns in cloud orchestration implementations, along with service level agreements and negotiations, portability, interoperability, standardization, resource demand profiling, resource pricing, profit maximizing and other runtime issues. The study, found that such cross-cutting concerns are addressed both by research initiatives, and to a larger extent by proprietary orchestration products, such as: Amazon Web Service OpsWorks, CFEngine, Docker, Heroku, Juju, Puppet, and VMWare vSphere.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Weerasiri et al [24] lists security as one of the crosscutting concerns in cloud orchestration implementations, along with service level agreements and negotiations, portability, interoperability, standardization, resource demand profiling, resource pricing, profit maximizing and other runtime issues. The study, found that such cross-cutting concerns are addressed both by research initiatives, and to a larger extent by proprietary orchestration products, such as: Amazon Web Service OpsWorks, CFEngine, Docker, Heroku, Juju, Puppet, and VMWare vSphere.…”
Section: Related Workmentioning
confidence: 99%
“…The set of high-level attacks is based on earlier research [18,20] and review articles [3,7,22,24]. VM Substitution Attack The adversary induces the orchestrator to launch a VM instance that contains hidden vulnerabilities, using a maliciously modified VM image instead of the tenant-selected image.…”
Section: High Level Attacksmentioning
confidence: 99%
“…The work of Weerasiri et al [48] presents a taxonomy and survey of cloud resource orchestration techniques, which includes autonomic orchestration strategies.…”
Section: Related Workmentioning
confidence: 99%
“…Existing orchestration systems [27,19,48] have been designed mainly for single data centres to help improve the make-span of workflow-based applications. QoS aspects related to networking have been traditionally addressed with Software Defined Networking (SDN) approaches [12], such as the one of Wang et al [47].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this way of procuring infrastructure introduces a layer of complexity that researchers may find hard to cope with. Configuring virtual resources requires substantial technical skills 5 , and it is generally a tedious and repetitive task when infrastructure is allocated on demand. Therefore, when running scientific applications on cloud there is a need for a methodology to aid this process.…”
Section: Introductionmentioning
confidence: 99%